Minding and mending the gap: Social psychological interventions to reduce educational disparities. (March 2015) - Spitzer, Brian; Aronson, Joshua
<x xml:space="preserve">Abstract</x> Background Achievement gaps continue to garner a great deal of attention both in academic and in popular circles. Many students continue to struggle despite broad educational reforms aimed at narrowing these gaps in learning and performance. Aims In this article, we review a number of social psychological interventions that show promise in reducing gaps in achievement, not by addressing structural barriers to achievement, but by helping students cope with threats to their identity that impair intellectual functioning and motivation. For example, interventions involving meditation, role models, emotional reappraisal, growth mindsets, imagining possible selves, self‐affirmations, belongingness and cooperative learning have been shown to ameliorate threats to identity and raise achievement. We describe and evaluate these social psychological interventions. Arguments Many achievement gaps involve a psychological predicament: a threat to one's social identity or to one's sense of belonging. Students' implicit theories – how they mind the gap – can act as barriers to their success. By helping students cope with these threats, these theory‐based interventions represent a genuine advance in the way schools may reduce gaps in achievement. Conclusion These interventions show how students' educational success depends partly on fluid aspects of context – how tasks are framed, who else is in the room, or what they believe about intelligence. Because of this fluidity, these interventions may not work in all settings. Achievement gaps are ultimately caused by a variety of factors, both objective and subjective that produce inequality. The research reviewed here suggests that even without changes in objective barriers to success, brief psychological interventions can narrow what many see as intractable gaps in academic achievement.